1983
DOI: 10.1111/j.1550-7408.1983.tb05463.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of the Adoral Ciliary Zone of Entodinium Stein (Ciliophora, Entodiniomorphida)

Abstract: The adoral ciliary zone of the rumen ciliates, Entodinium spp., was observed topographically in the SEM. The upper side of the anterior end of the body was indented by the vestibulum, which had cilia arranged on its right wall and ribs along the left wall. The adoral ciliary zone could be divided into at least two arrangements. The outer ciliary zone had many membranelle‐like structures, which consisted of cilia arranged radially from the body axis. Each membranelle‐like structure consisted of two rows of abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The present observations revealed that not only the bases of cilia in the outer and inner adoral zones were arranged uniformly as indicated by former investigators ( 2 , 1 3 , but also that the cilia of the outer adoral zone were aggregated to form ciliary tufts in contrast with the cilia of the inner zone, which had a random arrangement. Such an arrangement of cilia of the adoral zone closely resembles that of Entodinium (7), which is classified as an entodiniomorphid ciliate like Cycloposthiurn. Nevertheless, despite the similarities in the inner zone, differences exist between both genera.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The present observations revealed that not only the bases of cilia in the outer and inner adoral zones were arranged uniformly as indicated by former investigators ( 2 , 1 3 , but also that the cilia of the outer adoral zone were aggregated to form ciliary tufts in contrast with the cilia of the inner zone, which had a random arrangement. Such an arrangement of cilia of the adoral zone closely resembles that of Entodinium (7), which is classified as an entodiniomorphid ciliate like Cycloposthiurn. Nevertheless, despite the similarities in the inner zone, differences exist between both genera.…”
Section: Discussionmentioning
confidence: 70%
“…packed cilia arising from a packet of kinetosomes (1). Previously, we reported that species of Entodinium, one of the entodiniomorphid genera inhabiting the rumen, have two types of ciliary zones on the peristome and suggested that these respective ciliary zones would play useful roles for movement and ingestion of food (7). The present paper describes the adoral ciliary zone of other entodiniomorphids, Cycloposthium spp., commonly inhabiting the large intestine of the horse.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…His first studies were observations on the adoral ciliary zone by scanning electron microscopy (Imai et al. , ). He continued these studies by refined silver impregnation (Ito and Imai ,b, , ; Ito et al.…”
mentioning
confidence: 99%